MARKETING CHANNEL OF THE TILAPIA IN HARAU SUB DISTRICT - Indah Kemala Sari, Regia (CV. Radja Publika, 2021)
This study aims to analyze the flow of tilapia trade in Harau Regency and the function of the trading system carried out in marketing tilapia in Harau Regency. The research was conducted in Solok Bio-Bio Village, Harau Sub District, Lima Puluh Kota Regency. The research sample was tilapia cultivation farmers selected by random sampling and tilapia marketing channels in Solok Bio Bio Village, Harau Sub District, namely traders and retailers using the snowball sampling method. The results showed that there were three patterns of tilapia marketing channels in Harau Sub District, namely Channel 0: Farmers → Final consumers; Channel II: Farmers → Retailers → Final consumers; Channel III : Farmers → wholesalers → Retailer → Final Consumers. The trading functions carried out include the functions of selling, buying, grading, transporting, storing and facilitating.